KONVENSI HAK ANAK SEBAGAI INSTRUMEN PENANGANAN ANAK-ANAK KORBAN KEKERASAN DAN EKSPLOITASI - Iin Karita Sakharina; S.M. Noor; Marcel Hendrapati; Aidir Amin Daud; Abdul Maasba Magassing; Kadarudin Kadarudin (The Juris, 2018)
Children as entrusted by God must be guarded and given protection from all kinds of crimes that can happen anytime and anywhere. As a form of con- cern for the international community, several international legal instruments are made both in the form of declarations and conventions which basically regulate the types of children's rights that must be protected by anyone, as well as forms of crimes against children's rights. International instruments on the protection of children's rights as set out in United Nations Resolution No. 44/25 dated November 20, 1989 concerning the Convention on the Rights of the Child.